ANALYSIS OF THE RELATIONSHIP BETWEEN SANITATION HYGIENE, FOOD QUALITY, AND SERVICE QUALITY TOWARDS INPATIENT SATISFACTION LEVEL IN FOOD PROVISION AT WAVA HUSADA HOSPITAL KEPANJEN - Ningrum, Sri Ayu; Nurmayanti, Rani; Hakimah, Nurul (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2025)
Abstract Background: This study examines patient satisfaction with hygiene and sanitation, food quality, and service quality in the food service at Wava Husada Hospital in Kepanjen. Hospital food quality plays a crucial role in supporting patient recovery, in addition to medication. Food tailored to the patient's condition serves as a supporting factor for healing. Furthermore, food and room cleanliness also influence comfort and accelerate the recovery process. Methods: The research used a quantitative descriptive approach, using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) to measure patient satisfaction, and the Spearman correlation test to determine the relationship between variables. Data were obtained through questionnaires distributed to patients who had received food service at the hospital. Results: The study showed a CSI score of 81.3%, indicating that patients were very satisfied with hygiene and sanitation, food quality, and service quality. However, based on the IPA analysis, seven out of 35 aspects needed further attention to improve service quality. Spearman's correlation test showed no significant relationship between sanitation hygiene, food quality, and service quality and patient satisfaction (p-value > 0.05). Conclusion: Patient satisfaction is very high, although improvements are needed in several areas to provide optimal service. Keywords : Hygiene sanitation, Food Quality, Service Quality, Patient Satisfaction, Hospital